Structural and dynamics behavior of an Endoglucanase from Fusarium Oxysporum in vacuum, emplicit solvent models - Noorbatcha, Ibrahim Ali; Waesoho, Shukree; Salleh, Hamzah Mohd. (2010)
Petroleum sourced fuels are recognized as unsustainable energies owing to depleting supplies and the accumulation of carbon dioxide in the atmosphere cause by the contribution of these fuels. Renewable sourced fuels, biofuels are necessary for environmental and economic sustainability. In biofuels production such as bioethanol, Fusarium oxysporum is a good source of cellulase, endoglucanases and xylanases, and especially due to its ability to directly convert cellulose and hemicellulose into ethanol. Recently our laboratory has obtained the gene of endoglucanase from Fusarium oxysporum which has 99% amino acid sequence identity with known crystal structure of endoglucanase (3OVW) from Fusarium oxysporum. Due to the potential applications of these enzymes in biofuel production, various computational attempts have been made to model and design enzymes with enhanced functionalities. Even though these studies have been traditionally carried out under vacuum environment, several approaches to include solvent environments in modelling these enzymes have been made recently. However, the effects of using different models for solvents on the final outcome of the dynamics simulations have not yet been fully understood. Here we present our work on molecular dynamics studies of our endoglucanase in implicit and explicit solvent models for better understanding of the effects of these approaches on the behaviour of endoglucanase.